Activities of daily living measurement after ischemic stroke: Rasch analysis of the modified Barthel Index. Issue 9 (5th March 2021) - Yang, Hongyan; Chen, Yuanyuan; Wang, Jianmiao; Wei, Hui; Chen, Yanqin; Jin, Jingfen
Abstract : Abstract: In patients with ischemic stroke, activities of daily living were used as an outcome indicator, and correct assessment is very important. We sought to examine the reliability and validity of the modified Barthel Index as an evaluation tool of activities of daily living in ischemic stroke patients by applying the Rasch analysis. We used a prospectively collected cohort of ischemic stroke patients in the department of neurology. Rasch analysis was used for evaluating the reliability and validity of the modified Barthel Index. A total of 231 patients were included in the analysis. The average of modified Barthel Index was 36.2 ± 17.8. The modified Barthel Index had high reliability of 0.88. There were no extremely mismatched items, and considered unidimensional, but the Point-Measure of bowels and bladder were 0.27, extremely lower than other items. The scale was stable in different sex and age, but had notable differential item functioning in muscle strength of the limbs. Rating categories were not functioning adequately in items. The item difficulty and patient ability were not matched, with a difference of 1.17 logics. 29.4% patients, no easy items could match their ability. The modified Barthel Index had high reliability but a relatively bad matching degree between item difficulty and patient ability. It still needs further improvement to reflect the activities of daily living in ischemic stroke patients.